Kajian Hadis mengenai Masjid Ramah Perkembangan Anak - Wakhid Hasyim (Jurnal Living Hadis, 2018)
In Islam, salat becomes one of the rituals that must be done by every individual. To be able to carry out continuously, discipline lead individuals. Ideally, the habit of praying has been done since the early age,therefore, parents often invite their children to perform prayers together in order to teach them a habituation. Obstacles felt by parents when they ask to pray in a congregation in the mosque, where children mostly active and rowdy,they may disrupt the concentration of other worshipers.Such places then "banned", either directly or indirectly, small children joining the congregational prayers in the mosque. This raises the emergence of child-friendly mosque, some muslims hold room for children to love the mosque.It is necessary to trace the source of reference to this issue. Based on the search, there are some traditions that show the participation of children in the congregational prayers in the mosque. Based on the analysis of sanad and matan hadis intended, it can be concluded that the Prophet ever allowed children to participate in the congregational prayers in the mosque. While in psychology's view, habituation as a child affects the later adulthood. Since violence in children - both physical and verbal - in reproving a child, when doing noisy in the mosque,may affects a bad impact in the long run, it better to be outlawed. As a result of this consciousness, some places have provided space for children to be able to perform activities in the mosque.